Determination of Residential Electrical Load Components In Iraqi North Region - Al-Hafidh, Majid. S.; Al-Nama, Mudhafar A.; Al-Fahadi, Azher S. (Iraqi Journal for Electrical and Electronic Engineering, 2018)
The residential electrical load in the city of Mosul as well as in most of cities in Iraq, is the major problem for the administration of electricity distribution. Since this kind of load is increasing drastically compared with other loads such as industrial, agricultural tourism and others which are declining for the last two decades due to unstable condition of the county. The residential electrical load components must be determined to solve the problems resulting from the significant increase in this load. This research aims to conduct a field survey to find out and identify the components of the residential electrical load ratios and qualitative change in the months of the year. The survey was conducted in the city of Mosul in northern Iraq. T he results were analyzed, and a number of recommendations were given to rationalize consumption.